2020
DOI: 10.1002/jbm4.10399
|View full text |Cite
|
Sign up to set email alerts
|

Folate and Vitamin B‐12 Status Is Associated With Bone Mineral Density and Hip Strength of Postmenopausal Chinese‐Singaporean Women

Abstract: The role of micronutrients such as folate and vitamin B-12 in bone quality has been widely studied with conflicting results. Ethnicity seems to play a large role on nutrient intake, as diet varies across cultures. In this study, we examined the relationships of BMD, proximal femur strength, and bone resorption with plasma folate and vitamin B-12 in a cohort of 93 healthy postmenopausal women of Chinese-Singaporean descent. The parameters examined were areal (aBMD) and volumetric BMD (vBMD) of the proximal femu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Vitamin K is known as a cofactor for the optimal mineralization of bone and is positively associated with BMD [ 11 ]. In addition, several epidemiologic studies found a significant relationship between high folate intake/concentrations and increased BMD or reduced fracture risk [ 7 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin K is known as a cofactor for the optimal mineralization of bone and is positively associated with BMD [ 11 ]. In addition, several epidemiologic studies found a significant relationship between high folate intake/concentrations and increased BMD or reduced fracture risk [ 7 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other critical nutrients for a vegan diet are long-chain n-3 fatty acids [ 10 ], vitamins (B12, A) [ 10 ], or minerals (zinc, selenium, iodine) [ 10 ], which are also related to bone health [ 8 ]. On the other hand, vegetarian and vegan diets provide important nutrients that protect bone, e.g., vitamin K [ 7 , 8 , 11 ] and folate [ 7 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The criterion for menopause is that menstruation has stopped for more than 12 months [11]. The diagnosis of T2DM is based on the standards of the American Diabetes Association [12], and the diagnosis criteria of osteoporosis refer to the diagnostic criteria established by the Chinese Society of Osteoporosis and Bone Mineral Diseases [13]. After diagnosis, the participants were divided into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Folate is essential for thymidine synthesis and thus for DNA formation and any cell division hence its role in the formation of red blood cells and healthy cell growth and function [67]. It is also an important nutrient involved in bone protection [69][70][71].…”
Section: Folatementioning
confidence: 99%